Tasting life twice : literary lesbian fiction by new American writers - Levy, E. J. (Ellen J.) (New York : Avon Books, 1995)
Versed in sexual politics and fluent in the language of alienation, these 25 short works chart new territories without the maps or compasses of social convention. This bravura collection showcases the fierce power and startling diversity of contemporary lesbian writing. Includes early work by acclaimed emerging talents such as Cheryl Strayed, Stephanie Grant, and Mei Ng, as well as stunning pieces by Carole Maso, Mary Gaitskill, Ana Castillo, Rebecca Brown, and others.
The bay of angels / Carole Maso
Keywords: Lesbians -- Fiction; Lesbians' writings, American; Gay fiction